1999
DOI: 10.21608/erjm.1999.72449
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach To Improve The Performance Of FuzzyLogic Based Controllers For Systems With Wide Range disturbances And Uncertain Parameters

Abstract: Applications offuzzy logic controllers have proved that a tuning algorithm must be added to improve its perfomance against the system disturbances. The tuning methodr represent an additional costs and complexiry for implementation. This paper, presents a novel method which implies a self-tuned c o n t r o h capable of damping the system oscillations whatever the disturbance changes. Moreover, this controller is robust to a degree that permits more than 2500% parameters uncertainties to be considered. The idea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In four IEEE-SSR-Biographies, published at 1976, 1979, and 1991 rupectively, holding more than 300 papers for SSR studies, it is found that in many of them the SSR-Countermeasures are only concerned with application of excitation system enhancement controllers for damping the SSR oscillations. Advanced control strategies such as fuzzy logic controllers and neural networks are also introduced to the power system stabilizers [5,14]. All the above controllers can be categorized as electrical SSR countermeasures.…”
Section: Introductionmentioning
confidence: 99%
“…In four IEEE-SSR-Biographies, published at 1976, 1979, and 1991 rupectively, holding more than 300 papers for SSR studies, it is found that in many of them the SSR-Countermeasures are only concerned with application of excitation system enhancement controllers for damping the SSR oscillations. Advanced control strategies such as fuzzy logic controllers and neural networks are also introduced to the power system stabilizers [5,14]. All the above controllers can be categorized as electrical SSR countermeasures.…”
Section: Introductionmentioning
confidence: 99%